Taro Lectin Can Act as a Cytokine-Mimetic Compound, Stimulating Myeloid and T Lymphocyte Lineages and Protecting Progenitors in Murine Bone Marrow - Erika Bertozzi de Aquino Mattos; Patricia Ribeiro Pereira; Lyris Anunciata Demétrio Mérida; Anna Carolina Nitzsche Teixeira Fernandes Corrêa; Maria Paula Vigna Freire; Vania Margaret Flosi Paschoalin; Gerlinde Agate Platais Brasil Teixeira; Maria de Fátima Brandão Pinho; Maurício Afonso Verícimo (MDPI AG, 2021)
Taro (Colocasia esculenta) corm is traditionally consumed as a medicinal plant to stimulate immune responses and restore a health status. Tarin, a taro lectin, is considered responsible for the immunomodulatory effects of taro. In the present study, in order to investigate the effects of tarin on bone marrow hematopoietic population, murine cells were stimulated with tarin combined with a highly enriched conditioned medium containing either IL-3 or GM-CSF. Cells challenged with tarin proliferated in a dose-dependent manner, evidenced by the increase in cell density and number of clusters and colonies. Tarin exhibited a cytokine-mimetic effect similar to IL-3 and GM-CSF, increasing granulocytic cell lineage percentages, demonstrated by an increase in the relative percentage of Gr-1+ cells. Tarin does not increase lymphocytic lineages, but phenotyping revealed that the relative percentage of CD3+ cells was increased with a concomitant decrease in CD19+ and IL-7Rα+ cells. Most bone marrow cells were stained with tarin-FITC, indicating non-selective tarin binding, a phenomenon that must still be elucidated. In conclusion, taro corms contain an immunomodulatory lectin able to boost the immune system by promoting myeloid and lymphoid hematopoietic progenitor cell proliferation and differentiation.